The Association Between Solid Fuel Use and Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Hyperplasia in Sichuan, China: Cross-Sectional Study - Qiming Yuan; Xianghong Zhou; Li Ma; Boyu Cai; Zilong Zhang; Linghui Deng; Dan Hu; Zhongyuan Jiang; Mingda Wang; Qiang Wei; Shi Qiu (JMIR Public Health and Surveillance)
Abstract BackgroundBenign prostatic hyperplasia (BPH) is a global age-related disease. It has been reported that over half of the Chinese male population aged 70 years or older are experiencing BPH. Solid fuel, which is the major source of household air pollution, has been reportedly associated with several adverse events, including sex hormone disorders. Due to the certain relationship between sex hormone levels and prostate disease, the relationship between solid fuel use and lower urinary tract symptoms (LUTSs) suggestive of BPH (LUTS/BPH) deserves further exploration. ObjectiveThis study mainly aimed to investigate the association between solid fuel use and LUTS/BPH. MethodsThe data used in this study were obtained from the West China Natural Population Cohort Study. Household energy sources were assessed using questionnaires. LUTS/BPH was evaluated based on participant self-reports. We performed propensity score matching (PSM) to reduce the influence of bias and unmeasured confounders. The odds ratio (OR) and 95% CI of LUTS/BPH for the solid fuel group compared with the clean fuel group were calculated. We also conducted stratified analyses based on BMI, metabolic syndrome, waist to hip ratio, drinking status, smoking status, and age. ResultsA total of 5463 participants were included in this study, including 399 solid fuel users and 5064 clean fuel users. After PSM, the solid fuel group included 354 participants, while the clean fuel group included 701 participants. Solid fuel use was positively correlated with LUTS/BPH before and after PSM (OR 1.68, 95% CI 1.31‐2.15 and OR 1.81, 95% CI 1.35‐2.44, respectively). In stratified analyses, the OR of the nonsmoking group was higher than that of the smoking group (OR 2.56, 95% CI 1.56‐4.20 and OR 1.47, 95% CI 0.99‐2.18, respectively). Similarly, the OR of the nondrinking group was higher than that of the drinking group (OR 2.70, 95% CI 1.46‐4.99 and OR 1.48, 95% CI 1.01‐2.17, respectively). ConclusionsA positive correlation between solid fuel use and LUTS/BPH was observed. The results suggest that improving fuel structure for household cooking and other household needs can possibly help reduce the risk of LUTS/BPH.